PC / ABS alloy and preparation method and application thereof

By adding modified graphene, KH550 and calcium sources to the PC/ABS alloy, the problems of poor deformation and electroplating performance of the alloy during the heat treatment process are solved, and the effects of high impact strength and high electroplating pass rate are achieved.

CN119798912AActive Publication Date: 2025-04-11ZHONGSHAN DIANSHI PLASTIC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411821158.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

PC/ABS alloys are prone to deformation during heat treatment. Improving their heat resistance will lead to poor electroplating performance, peeling and cracking of the plating layer.

Method used

By adding modified graphene, KH550 and calcium sources to the PC/ABS alloy, the bonding strength between the plating and the alloy is improved, structural stability and electroplating pass rate are improved.

Benefits of technology

The high impact strength and excellent electroplating performance of PC/ABS alloy are achieved, and the electroplating pass rate is above 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183139980000011
    Figure BDA0005183139980000011
  • Figure BDA0005183139980000021
    Figure BDA0005183139980000021
  • Figure BDA0005183139980000022
    Figure BDA0005183139980000022
Patent Text Reader

Abstract

The invention discloses a PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) alloy as well as a preparation method and application thereof, and relates to the technical field of polymer composite materials. The PC / ABS alloy comprises the following components: PC, ABS, modified graphene, KH550 and a calcium source. The modified graphene, KH550 and Ca can synergistically improve the bonding strength of the coating and the PC / ABS alloy, so that the overall structure is more stable, the electroplating qualification rate reaches 95% or above, and the modified graphene, KH550 and Ca can synergistically improve the mechanical strength, so that the PC / ABS alloy has high impact strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a PC / ABS alloy and a preparation method and application thereof. Background Art

[0002] PC / ABS alloy is an alloy formed by blending polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS). It has both the good impact and formability of ABS and the excellent impact and heat resistance of PC. It is widely used in electroplating products such as automotive parts, home appliances, and sanitary ware.

[0003] However, PC / ABS alloys are prone to deformation and other problems during heat treatment. In the related art, the heat resistance of PC / ABS alloys is often improved by increasing the PC content in the alloys, but this also easily leads to poor electroplating performance of PC / ABS alloys, low peeling strength, easy plating shedding, cracking and other problems, and low electroplating yield. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a PC / ABS alloy having good electroplating performance and mechanical strength.

[0005] The invention also provides a method for preparing the PC / ABS alloy.

[0006] The invention also provides application of PC / ABS alloy.

[0007] The PC / ABS alloy according to the first aspect of the present invention comprises the following components:

[0008] PC, ABS, modified graphene, KH550 and calcium source.

[0009] The PC / ABS alloy according to the embodiment of the present invention has at least the following beneficial effects:

[0010] In the PC / ABS alloy of the embodiment, modified graphene, KH550 and Ca can improve the bonding strength between the coating and the PC / ABS alloy, making the overall structure more stable, the electroplating pass rate reaching more than 95%, and synergistically improve the mechanical strength, so that the PC / ABS alloy has high impact strength.

[0011] According to some embodiments of the present invention, the PC / ABS alloy comprises, by weight:

[0012]

[0013]

[0014] According to some embodiments of the present invention, the PC / ABS alloy comprises, by weight:

[0015]

[0016] According to some embodiments of the present invention, the PC / ABS alloy comprises, by weight:

[0017]

[0018] According to some embodiments of the present invention, the PC / ABS alloy comprises, by weight:

[0019]

[0020] According to some embodiments of the present invention, the PC has a melt flow rate of 5 g / 10 min to 20 g / 10 min at 300° C. and 1.2 kg according to ISO 1133. For example, it may be 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min, 11 g / 10 min, 12 g / 10 min, 13 g / 10 min, 14 g / 10 min, 15 g / 10 min, 16 g / 10 min, 17 g / 10 min, 18 g / 10 min, 19 g / 10 min or 20 g / 10 min.

[0021] According to some embodiments of the present invention, the PC has a heat deformation temperature of 120°C to 130°C at 1.8 MPa according to ISO 75-2. For example, it may be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C.

[0022] According to some embodiments of the present invention, the PC has a Vicat softening temperature of 140°C to 150°C at 50N and 50°C / h according to ISO 306. For example, it may be 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C or 150°C.

[0023] According to some embodiments of the present invention, the melt flow rate of the ABS at 220°C and 10kg according to ASTM D1238 is 15 g / 10min to 30 g / 10min. 22 g / 10min. For example, it can be 15 g / 10min, 16 g / 10min, 17 g / 10min, 18 g / 10min, 19 g / 10min, 20 g / 10min, 21 g / 10min, 22 g / 10min, 23 g / 10min, 24 g / 10min, 25 g / 10min, 26 g / 10min, 27 g / 10min, 28 g / 10min, 29 g / 10min or 30 g / 10min.

[0024] According to some embodiments of the present invention, the heat deformation temperature of ABS according to ASTM D648 is 95°C to 105°C. For example, it may be 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, 101°C, 102°C, 103°C, 104°C or 105°C.

[0025] According to some embodiments of the present invention, the Vicat softening temperature of ABS according to ASTM D1525 is 100° C. to 110° C. For example, it may be 100° C., 101° C., 102° C., 103° C., 104° C., 105° C., 106° C., 107° C., 108° C., 109° C. or 110° C.

[0026] According to some embodiments of the present invention, the method for preparing modified graphene comprises the following steps:

[0027] A mixture of graphene oxide, a copper source, a sulfur source and PVP is prepared, reacted at 170° C. to 190° C., and solid-liquid separation is performed, and the solid phase is the modified graphene.

[0028] According to some embodiments of the present invention, in the method for preparing modified graphene, the reaction time is 10 h to 14 h, for example, 10 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h or 14 h.

[0029] According to some embodiments of the present invention, in the method for preparing modified graphene, the reaction medium is water.

[0030] According to some embodiments of the present invention, the graphene oxide is pre-treated by ultrasonic dispersion.

[0031] According to some embodiments of the present invention, the ultrasonic dispersion pretreatment time is 15 min to 30 min. For example, it can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min.

[0032] According to some embodiments of the present invention, the temperature of the ultrasonic dispersion pretreatment is 20°C to 30°C. For example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C.

[0033] According to some embodiments of the present invention, the ultrasonic power of the ultrasonic dispersion pretreatment is 80W to 120W. For example, it can be 80W, 82W, 84W, 86W, 88W, 90W, 92W, 94W, 96W, 98W, 100W, 102W, 104W, 106W, 108W, 110W, 112W, 114W, 116W, 118W or 120W.

[0034] According to some embodiments of the present invention, the graphene oxide is a single-layer graphene oxide.

[0035] According to some embodiments of the present invention, the sheet diameter of the graphene oxide is 0.5 μm to 5 μm. For example, it can be 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm or 5 μm.

[0036] According to some embodiments of the present invention, the thickness of the graphene oxide is 0.8 nm to 1.2 nm, for example, 0.8 nm, 0.82 nm, 0.84 nm, 0.86 nm, 0.88 nm, 0.9 nm, 0.92 nm, 0.94 nm, 0.96 nm, 0.98 nm, 1 nm, 1.02 nm, 1.04 nm, 1.06 nm, 1.08 nm, 1.1 nm, 1.12 nm, 1.14 nm, 1.16 nm, 1.18 nm or 1.2 nm.

[0037] According to some embodiments of the present invention, the copper source includes at least one of copper nitrate, copper acetate, and copper chloride.

[0038] According to some embodiments of the present invention, the sulfur source includes at least one of thioacetamide, sodium sulfide, sodium thiosulfate, and L-cysteine.

[0039] According to some embodiments of the present invention, the mass molar ratio of the graphene oxide to the copper source and the sulfur source is 1g: (0.0004mol~0.0006mol): (0.0004mol~0.0006mol).

[0040] According to some embodiments of the present invention, the mass molar ratio of the graphene oxide to the copper source and the sulfur source is 1g: (0.00045mol~0.00055mol): (0.00045mol~0.00055mol).

[0041] According to some embodiments of the present invention, the mass molar ratio of the graphene oxide to the copper source and the sulfur source is 1g: (0.0005mol~0.00055mol): (0.0005mol~0.00055mol).

[0042] According to some embodiments of the present invention, the reaction concentration of graphene oxide is 0.8 mg / mL to 1.2 mg / mL, for example, 0.8 mg / mL, 0.85 mg / mL, 0.9 mg / mL, 0.95 mg / mL, 1 mg / mL, 1.05 mg / mL, 1.1 mg / mL, 1.15 mg / mL or 1.2 mg / mL.

[0043] According to some embodiments of the present invention, the calcium source is a calcium-containing compound.

[0044] According to some embodiments of the present invention, the calcium source includes at least one of calcium oxide, calcium hydroxide, calcium carbonate, and calcium oxalate.

[0045] According to some embodiments of the present invention, in the method for preparing the modified graphene, the mass ratio of the PVP to the graphene oxide is (80-120): 1. For example, it may be 80:1, 82:1, 84:1, 86:1, 88:1, 90:1, 92:1, 94:1, 96:1, 98:1, 100:1, 102:1, 104:1, 106:1, 108:1, 110:1, 112:1, 114:1, 116:1, 118:1 or 120:1.

[0046] According to some embodiments of the present invention, the PC / ABS alloy further includes 0-1 parts of additives by weight, for example, 0 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 part of additives.

[0047] According to some embodiments of the present invention, the auxiliary agent includes at least one of a pigment, an antioxidant, and a lubricant.

[0048] According to some embodiments of the present invention, the antioxidant includes at least one of antioxidant 1010, antioxidant 1790, antioxidant 619F, antioxidant 626, antioxidant 1076, and antioxidant 168. The antioxidant is obtained by mixing antioxidant 1076 and antioxidant 168 in a mass ratio of 1:(0.9-1.1).

[0049] According to some embodiments of the present invention, the PC / ABS alloy includes 0.1 to 0.5 parts of antioxidant, if any. For example, it may include 0.1, 0.2, 0.3, 0.4 or 0.5 parts of antioxidant.

[0050] According to some embodiments of the present invention, the lubricant includes at least one of polyethylene wax, silicone masterbatch, N,N'-ethylene bisstearamide, pentaerythritol stearate and erucamide.

[0051] According to some embodiments of the present invention, the PC / ABS alloy includes 0.1 to 0.5 parts of lubricant, if any. For example, it may include 0.1, 0.2, 0.3, 0.4 or 0.5 parts of lubricant.

[0052] The method for preparing the PC / ABS alloy according to the second aspect of the present invention comprises the following steps:

[0053] The components are mixed and melt-extruded to obtain the PC / ABS alloy.

[0054] According to some embodiments of the present invention, the melt extrusion conditions include: the temperature of zone 1 is 225°C to 235°C, the temperature of zone 2 is 235°C to 245°C, the temperature of zone 3 is 245°C to 255°C, the temperature of zone 4 is 250°C to 260°C, the temperature of zone 5 is 255°C to 265°C, and the temperature of zone 6 is 235°C to 245°C.

[0055] According to some embodiments of the present invention, the melt extrusion conditions include: a rotation speed of 150 r / min to 300 r / min.

[0056] According to some embodiments of the present invention, the melt extrusion conditions include: the aspect ratio of the twin-screw extruder is 30-35:1.

[0057] According to the third aspect of the present invention, the PC / ABS alloy is used in electroplating products.

[0058] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0059] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0060] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0061] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0062] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0063] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0064] Unless otherwise specified, “room temperature” refers to (25±5)℃.

[0065] In the embodiments and comparative examples of the present invention, the grade of PC is 6555 (Covestro (Bayer) of Germany), the melt flow rate at 300°C and 1.2kg according to ISO1133 is 10g / 10min, the heat deformation temperature at 1.8MPa according to ISO 75-2 is 125°C, and the Vicat softening temperature at 50N and 50°C / h according to ISO 306 is 144°C;

[0066] The grade of ABS is PA757 (Chi Mei Company, Taiwan, China), with a melt flow rate of 22 g / 10 min at 220°C and 10 kg according to ASTM D1238, a heat deformation temperature of 99°C according to ASTM D648, and a Vicat softening temperature of 105°C according to ASTM D1525;

[0067] The antioxidant is obtained by mixing antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1;

[0068] The lubricant is pentaerythritol stearate (lubricant PETS);

[0069] Graphene oxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. It is a single-layer graphene oxide, numbered XF002-2, with a sheet diameter of 0.5 μm to 5 μm and a thickness of 0.8 nm to 1.2 nm.

[0070] In the embodiments and comparative examples of the present invention, the steps of preparing the modified graphene are as follows:

[0071] (1) mixing graphene oxide with deionized water (the final concentration of graphene oxide is 1 mg / mL), and ultrasonically dispersing at room temperature for 20 min, with an ultrasonic power of 100 W and an ultrasonic temperature controlled below 30° C. to obtain a graphene oxide dispersion;

[0072] (2) Add 1 mg of copper nitrate, 0.42 mg of sodium sulfide and 1 g of PVP to 10 mL of graphene oxide dispersion, and perform hydrothermal reaction at 180° C. for 12 h. After the reaction solution is cooled to room temperature, centrifuge at 10,000 rpm for 20 min, wash, and obtain modified graphene.

[0073] Example 1

[0074] This example provides a PC / ABS alloy, which is prepared from the following components in parts by weight:

[0075]

[0076]

[0077] The preparation method of the PC / ABS alloy is as follows:

[0078] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0079] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0080] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0081] Example 2

[0082] This example provides a PC / ABS alloy, which is prepared from the following components in parts by weight:

[0083]

[0084] The preparation method of the PC / ABS alloy is as follows:

[0085] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0086] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0087] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0088] Example 3

[0089] This example provides a PC / ABS alloy, which is prepared from the following components in parts by weight:

[0090]

[0091]

[0092] The preparation method of the PC / ABS alloy is as follows:

[0093] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0094] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0095] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0096] Example 4

[0097] This example provides a PC / ABS alloy, which is prepared from the following components in parts by weight:

[0098]

[0099] The preparation method of the PC / ABS alloy is as follows:

[0100] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0101] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0102] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0103] Example 5

[0104] This example provides a PC / ABS alloy, which is prepared from the following components in parts by weight:

[0105]

[0106]

[0107] The preparation method of the PC / ABS alloy is as follows:

[0108] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0109] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0110] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0111] Comparative Example 1

[0112] This example provides a PC / ABS alloy, which is different from Example 1 only in that modified graphene is omitted.

[0113] The PC / ABS alloy is prepared from the following components in parts by weight:

[0114]

[0115] The preparation method of the PC / ABS alloy is as follows:

[0116] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0117] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0118] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0119] Comparative Example 2

[0120] This example provides a PC / ABS alloy, which is different from Example 1 only in that KH550 is omitted.

[0121] The PC / ABS alloy is prepared from the following components in parts by weight:

[0122]

[0123] The preparation method of the PC / ABS alloy is as follows:

[0124] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0125] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0126] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0127] Comparative Example 3

[0128] This example provides a PC / ABS alloy, which is different from Example 1 only in that CaO is omitted.

[0129] The PC / ABS alloy is prepared from the following components in parts by weight:

[0130]

[0131] The preparation method of the PC / ABS alloy is as follows:

[0132] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0133] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0134] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0135] Comparative Example 4

[0136] This example provides a PC / ABS alloy, which is different from Example 1 only in that modified graphene, KH550 and CaO are omitted.

[0137] The PC / ABS alloy is prepared from the following components in parts by weight:

[0138]

[0139] The preparation method of the PC / ABS alloy is as follows:

[0140] S1. Weigh the corresponding mass parts of each component and add them into a high-speed mixer, and stir for 10 minutes at a stirring speed of 160 r / min to obtain a mixture;

[0141] S2, putting the mixed material into a twin-screw extruder, and obtaining a PC / ABS alloy through melt extrusion and cooling;

[0142] The conditions for melt extrusion are: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 255°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 240°C, and the rotation speed is 200r / min; the aspect ratio of the twin-screw extruder is 32:1.

[0143] Test example

[0144] The properties of the PC / ABS alloys of Examples 1 to 5 and Comparative Examples 1 to 4 were tested. The testing method is as follows:

[0145] (1) Electroplating bonding strength: According to GMW14668-2010 standard, the stretching speed is 100 mm / min and the angle is 90°.

[0146] (2) Electroplating pass rate: The samples to be tested were injection molded into 140mm*90mm*3mm samples for electroplating. The concentrations of concentrated sulfuric acid and chromic acid in the electroplating roughening solution were both 380g / L, the roughening temperature was 65℃, and the roughening time was 10min. Each group electroplated 100 samples, and professional electroplating technicians evaluated the electroplating conditions of the samples and calculated the pass rate.

[0147] (3) Impact strength: The sample to be tested was injection molded into a specimen of 80 mm*10 mm*4 mm and tested in accordance with ISO 179 standard with a notch depth of 2.0 mm.

[0148] The test results are shown in Table 1.

[0149] Table 1

[0150]

[0151]

[0152] The PC / ABS alloys of Examples 1 to 3 all have good electroplating performance (high electroplating bonding strength and high electroplating qualified rate) and mechanical strength. The omission of any one of modified graphene, KH550 and CaO will lead to poor performance.

[0153] In summary, the modified graphene, KH550 and CaO in the PC / ABS alloy of the present invention have a significant synergistic effect in improving electroplating performance and mechanical strength.

[0154] The embodiments of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A PC / ABS alloy, characterized in that: The components include: PC, ABS, modified graphene, KH550 and calcium source.

2. The PC / ABS alloy according to claim 1, characterized in that: In parts by mass, the PC / ABS alloy comprises: Preferably, in parts by mass, the PC / ABS alloy comprises:

3. The PC / ABS alloy according to claim 1 or 2, characterized in that: The PC has a melt flow rate of 5 g / 10 min to 20 g / 10 min at 300° C. and 1.2 kg according to ISO 1133; and / or, the PC has a heat deformation temperature of 120° C. to 130° C. at 1.8 MPa according to ISO 75-2; And / or, the PC has a Vicat softening temperature of 140°C to 150°C at 50N and 50°C / h according to ISO 306.

4. The PC / ABS alloy according to claim 1 or 2, characterized in that: The melt flow rate of the ABS at 220° C. and 10 kg according to ASTM D1238 is 15 g / 10 min to 30 g / 10 min; and / or, the heat deformation temperature of the ABS according to ASTM D648 is 95° C. to 105° C.; And / or, the Vicat softening temperature of the ABS according to ASTM D1525 is 100° C. to 110° C.

5. The PC / ABS alloy according to claim 1 or 2, characterized in that: The preparation method of the modified graphene comprises the following steps: A mixture of graphene oxide, a copper source, a sulfur source and PVP is prepared, reacted at 170° C. to 190° C., and solid-liquid separation is performed, and the solid phase is the modified graphene; Preferably, in the method for preparing modified graphene, the reaction time is 10 h to 14 h; Preferably, the mass molar ratio of the graphene oxide to the copper source and the sulfur source is 1 g: 0.0004 mol to 0.0006 mol: 0.0004 mol to 0.0006 mol.

6. The PC / ABS alloy according to claim 1 or 2, characterized in that: The calcium source includes at least one of calcium oxide, calcium hydroxide, calcium carbonate and calcium oxalate.

7. The PC / ABS alloy according to claim 1, characterized in that: The PC / ABS alloy further comprises 0 to 1 part of an additive in terms of mass fraction; preferably, the additive comprises at least one of a pigment, an antioxidant and a lubricant.

8. The PC / ABS alloy according to claim 7, characterized in that: The antioxidant includes at least one of antioxidant 1010, antioxidant 1790, antioxidant 619F, antioxidant 626, antioxidant 1076, and antioxidant 168; And / or, the lubricant includes at least one of polyethylene wax, silicone masterbatch, N,N'-ethylene bisstearamide, pentaerythritol stearate and erucamide.

9. The method for preparing the PC / ABS alloy according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components are mixed and melt-extruded to obtain the PC / ABS alloy.

10. Use of the PC / ABS alloy according to any one of claims 1 to 8 in electroplating products.

Citation Information

Patent Citations

  • High-heat-resistant high-binding-force electroplating PC / ABS alloy material and preparation method thereof

    CN106633769A

  • Electroplating PC / ABS alloy material suitable for door handle and preparation method of electroplating PC / ABS alloy material

    CN106633776A

  • Graphene oxide loaded copper sulfide composite material preparation method

    CN109573997A

  • PC / ABS composite material and preparation method thereof

    CN111234499A

  • Environment-friendly reinforced PC and ABS composite material and preparation method thereof

    CN112029258A